(3QSGdI dWg bWQjg GHf GdTjN eMehOs - (3Wg bWQjg Hf eMehOs
(3ChdgG (B:s
(3CeG HYO aEf cJGH GdTLQI GdchfjI JCdja GdEeGe GdZfj aVdg Yf Cf jTgQ s
(3BNQgG (B:s
(3hceGd EMSGf UfYg djGdi GdbOQ Ke s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3hbO cJHJ HBdg cGJHgs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdChbGa GdYGeI HWQGHdS GdZQH (B- (3djHjG (B(47) s
Keywords: (3GdeYGQa GdYGeIs